Re-Establishing Credible Nominal Anchors After a Financial Crisis : A Review of Recent Experience - Zanello, Alessandro (IMF Working Papers; Working Paper ;, 2003)
This paper studies the question of how to achieve monetary policy credibility and price stability after a financial crisis. We draw stylized facts and conclusions from ten recent cases: Brazil (1999); Bulgaria (1997); Ecuador (2000); Indonesia (1997); Korea (1997); Malaysia (1997); Mexico (1994), Russia (1998); Thailand (1997); and Turkey (2001). Among our conclusions, highlights include: (i) monetary policy alone cannot stabilize; (ii) floats bring nominal stability quickly in countries with low pre-crisis inflation and hard pegs have been at least narrowly successful for countries in deeper disarray; (iii) in floats, early and determined tightening brings nominal stability and does not appear more costly for output; (iv) monetary aggregate targeting rarely serves as a coherent framework for floats; informal or full-fledged inflation targeting offers more promise.